Вивчення структурних особливостей сплавів системи Ti–Zr–Ni після їх термообробки та гідрування - Карпець, М.В.; Солонін, Ю.М.; Веліканова, Т.А.; Фомічов, О.С.; Карпець, Ф.М.; Хомко, Т.В. (Видавничий дім "Академперіодика" НАН України, 2007)
By means of hot-stage X-Ray diffraction and X-Ray Rietveld methods, the phase compositions of as-casted, heat-treated, and sintered Ti–Zr–Ni alloys are investigated before and after their hydrogenation from the gas phase at a temperature of 260 °C and a pressure of 41 аtm. The conditions of the formation of the quasicrystal and approximant phases in Ti–Zr–Ni alloys are studied. It is shown that Ti–Zr–Ni alloys comprising quasicrystal and crystal approximant components absorb up to 2.5 mass. % hydrogen at the less volume effect as compared with alloys containing the С14 Laves phase or a cubic TiZr2Ni phase of the Ti2Ni-type.